PGMI STUDENTS' ABILITY TO DEVELOP SCIENCE LEARNING VIDEOS BASED ON PROBLEM BASED LEARNING MODELS - Pipih Nurhayati; Dzikra Fu’adiah; Mario Emilzoli (Jurnal Muara Pendidikan, 2022)
This study aims to determine the ability of PGMI students to integrate and develop MI science learning videos based on the PBL model. This study uses a quantitative descriptive method where the subject of this research is 30 students of the PGMI Study Program. Data were obtained through observation sheets, product assessment sheets and interview guidelines. The results showed that PGMI students had been able to integrate well (82.14) the PBL learning model in scenarios and the development of science learning videos in MI. PBL-based video learning is considered to be able to support students to learn independently (85,14). Technically, the assessment of sound and picture clarity still needs to be improved (67.86).